Inhibition of Thrombin Generation by the Oral Direct Thrombin Inhibitor Ximelagatran in Shed Blood from Healthy Male Subjects - Sarich, Troy C.; Eriksson, Ulf G.; Mattsson, Christer; Wolzt, Michael; Frison, Lars; Fager, Gunnar; Gustafsson, David (Thrombosis and Haemostasis, 2002)
Ximelagatran, an oral direct thrombin inhibitor, whose active form is melagatran, was studied using a model of thrombin generation in humans. Healthy male volunteers (18 per group) received ximelagatran (60 mg p.o.), dalteparin (120 IU/kg s.c.) or a control (water p.o.). Shed blood, collected after incision of the forearm with standardised bleeding time devices at pre-dose, and at 2, 4 and 10 h post-dosing, was analysed for markers of thrombin generation. Statistically significant reductions (p < 0.05) in levels of prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complex (TAT) in shed blood were detected at 2 and 4 h post-dosing in both the ximelagatran and dalteparin groups. Shed blood F1+2 and TAT levels had returned to pre-dose levels at 10 h post-dosing. Using a shed blood model, we demonstrate that the reversible thrombin inhibitor melagatran and, therefore, oral administration of ximelagatran, inhibits thrombin generation in humans after acute activation of coagulation.
Keywords: Oral direct thrombin inhibitor; ximelagatran; melagatran; thrombin generation; shed blood